IMPLEMENTASI GOOD CORPORATE GOVERNANCE TERHADAP KEPATUHAN KARYAWAN PT. SRI PAMELA MEDIKA NUSANTARA DI KOTA TEBING TINGGI - Mariana, Dina; Ginting, Budiman; Aflah, Aflah (Penerbit Lafadz Jaya, 2025)
This study aims to examine the influence of Good Corporate Governance (GCG) implementation on employee compliance at PT. Sri Pamela Medika Nusantara (SPMN) in Tebing Tinggi City. The application of GCG principles is considered crucial for enhancing operational efficiency and effectiveness, particularly in the healthcare sector, which demands high ethical and professional standards. This research adopts an empirical juridical approach with descriptive-analytical methods. Data were collected through interviews, literature reviews, documentation, and questionnaire distribution, followed by qualitative descriptive analysis. The findings indicate that the implementation of GCG principles at PT. SPMN has a significant impact on employee compliance levels. Key supporting factors include employees' strong understanding of GCG principles such as transparency, accountability, and fairnesswhich encourages adherence to company policies. Management commitment also plays a vital role in fostering a work environment conducive to optimal GCG implementation. However, challenges persist, including employees' lack of awareness of applicable regulations and an organizational culture that does not fully align with GCG principles. Non-compliance with GCG may lead to negative consequences for the company, such as reputational damage and legal risks. Persistent violations could result in legal actions, including employee termination or heavier sanctions, ultimately affecting the company’s sustainability and performance.